2013
DOI: 10.1080/17457300.2012.686040
|View full text |Cite
|
Sign up to set email alerts
|

An examination of some safety issues among commercial motorcyclists in Nigeria: a case study

Abstract: The reduction of road crashes and injuries among motorcyclists in Nigeria requires a system inquiry into some safety issues at pre-crash, crash and post-crash stages to guide action plans. This paper examines safety issues such as age restriction, motorcycle engine capacity, highway code awareness, licence holding, helmet usage, crash involvement, rescue and payment for treatment among commercial motorcyclists. The primary data derived from a structured questionnaire administered to 334 commercial motorcyclist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Throughout most of Africa, motorcycles are used as both public and private modes of transportation [ 7 , 8 ]. For example, motorcycles have become increasingly popular over the last decade, due to their ability to navigate through poor road conditions and congested traffic compared to other larger motor vehicles [ 7 , 9 ]. However, this trend has also resulted in an increase in mortality and morbidity rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout most of Africa, motorcycles are used as both public and private modes of transportation [ 7 , 8 ]. For example, motorcycles have become increasingly popular over the last decade, due to their ability to navigate through poor road conditions and congested traffic compared to other larger motor vehicles [ 7 , 9 ]. However, this trend has also resulted in an increase in mortality and morbidity rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, motorcycles have become increasingly popular over the last decade, due to their ability to navigate through poor road conditions and congested traffic compared to other larger motor vehicles [ 7 , 9 ]. However, this trend has also resulted in an increase in mortality and morbidity rates [ 9 ]. Together, RTCs for motorcyclists, cyclists, and pedestrians account for more than 50% of head-related deaths [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Nigeria have observed that incidence of road traffic accidents and injuries in general are on the increase (Ikporukpo, 2004;Arosanyin et al, 2013;Osayomi, 2013). For instance, between January 2007 and June 2010, about 4076 people were killed and 12,994 injured in 4017 cases of accidents involving tankers in Nigeria (FRSC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In general, road traffic accidents literature in the country have focused on the spatial pattern, causes, magnitude, safety issues and socio-economic cost of road traffic accidents (Oyemade, 1973;Jegede, 1988;Asogwa, 1992;Osime et al, 2006;Filani and Gbadamosi, 2007;Ipingbemi, 2008;Ipingbemi, 2012;Atubi and Onokala, 2009;Arosanyin et al, 2013;Osayomi, 2013). Conspicuously absent from the literature are studies on explorative analyses of the spatial patterns and determinants of tanker accidents in the country.…”
Section: Introductionmentioning
confidence: 99%
“…En los factores del entorno, se determina que en la medida que aumenta el flujo de vehículos, los motociclistas están expuestos a mayor número de interacciones [49]. El volumen y flujo vehicular son factores asociados en los conflictos viales en motocicletas [50]. La infraestructura vial, así como la calidad del pavimento inciden en los accidentes [51].…”
Section: Factores Asociados Con La Accidentalidad De Las Motocicletasunclassified